Dual‐Mode, Anisotropy‐Encoded, Ratiometric Fluorescent Nanosensors: Towards Multiplexed Detection. Issue 63 (24th October 2018) - Rampazzo, Enrico; Bonacchi, Sara; Juris, Riccardo; Genovese, Damiano; Prodi, Luca; Zaccheroni, Nelsi; Montalti, Marco
Abstract: A nanosensor with dual‐mode fluorescence response to pH and an encoded identification signal, was developed by exploiting excitation energy transfer and tailored control of molecular organization in core–shell nanoparticles. Multiple signals were acquired in a simple single‐excitation dual‐emission channels set‐up. Abstract : A nanosensor with dual‐mode fluorescence response to pH and an encoded identification signal was developed by exploiting excitation energy transfer and tailored control of molecular organization in core–shell nanoparticles.